The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41598-018-27457-3
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Intravenous Lidocaine at Different Doses for Fentanyl-Induced Cough (FIC): A Meta-Analysis

Abstract: To evaluate whether different doses of intravenous lidocaine are effective at preventing fentanyl-induced cough (FIC), we searched PubMed, Scopus, Cochrane Library, EMBASE and Web of Science, according to predefined criteria, for all articles published until June 2017. A meta-analysis and subgroup analysis were performed by combining the reported incidence of FIC. The odds ratio (OR) was used as a summary statistic. Eleven articles were included, with 965 patients in the lidocaine group and 745 patients in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Another study found that 0.5 mg⋅kg −1 lidocaine had a significant effect and that increasing the concentration to 1.5 mg⋅kg −1 did not further reduce the incidence and severity of FIC ( Pandey et al, 2005 ). A recent meta-analysis also showed that both low (0.5–1 mg⋅kg −1 ) and high doses of lidocaine (1.5–2 mg⋅kg −1 ) were effective at reducing FIC incidence, there was no significant difference between low or high doses of lidocaine ( Tan et al, 2018 ). However, high doses of lidocaine may lead to arrhythmia and depression ( Schlimp and Wiedermann, 2005 ).…”
Section: Prevention and Treatment Of Fentanyl-induced Coughmentioning
confidence: 99%
“…Another study found that 0.5 mg⋅kg −1 lidocaine had a significant effect and that increasing the concentration to 1.5 mg⋅kg −1 did not further reduce the incidence and severity of FIC ( Pandey et al, 2005 ). A recent meta-analysis also showed that both low (0.5–1 mg⋅kg −1 ) and high doses of lidocaine (1.5–2 mg⋅kg −1 ) were effective at reducing FIC incidence, there was no significant difference between low or high doses of lidocaine ( Tan et al, 2018 ). However, high doses of lidocaine may lead to arrhythmia and depression ( Schlimp and Wiedermann, 2005 ).…”
Section: Prevention and Treatment Of Fentanyl-induced Coughmentioning
confidence: 99%
“…However, our study found the use of lidocaine was associated with a reduced risk of FIC owing to the arrhythmogenic effects of lidocaine. An appropriate dose of lidocaine can reduce the risk of FIC [ 37 ], and the prophylactic effect of intravenous lidocaine on the risk of opioid-induced cough has already demonstrated [ 38 , 39 ]. Fourth, the use of vecuronium can affect histamine release, which is involved in the onset of FIC [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of statistical significance in these groups may be explained by the small sample size and paucity of past studies. Premedicating with fentanyl leads to coughing, 36 which may interrupt the recording of airway events. In our study, the use of a subgroup analysis clarified these concerns, and the results were consistent in patients who were and who were not premedicated with fentanyl.…”
Section: Discussionmentioning
confidence: 99%